The role of bone in glenohumeral stability. Issue 12 (December 2018) - Di Giacomo, Giovanni; Piscitelli, Luigi; Pugliese, Mattia
Abstract : Shoulder stability depends on several factors, either anatomical or functional. Anatomical factors can be further subclassified under soft tissue (shoulder capsule, glenoid rim, glenohumeral ligaments etc) and bony structures (glenoid cavity and humeral head). Normal glenohumeral stability is maintained through factors mostly pertaining to the scapular side: glenoid version, depth and inclination, along with scapular dynamic positioning, can potentially cause decreased stability depending on the direction of said variables in the different planes. No significant factors in normal humeral anatomy seem to play a tangible role in affecting glenohumeral stability. When the glenohumeral joint suffers an episode of acute dislocation, either anterior (more frequent) or posterior, bony lesions often develop on both sides: a compression fracture of the humeral head (or Hill–Sachs lesion) and a bone loss of the glenoid rim. Interaction of such lesions can determine 're-engagement' and recurrence. The concept of 'glenoid track' can help quantify an increased risk of recurrence: when the Hill–Sachs lesion engages the anterior glenoid rim, it is defined as 'off-track'; if it does not, it is an 'on-track' lesion. The position of the Hill–Sachs lesion and the percentage of glenoid bone loss are critical factors in determining the likelihood of recurrent instability and in managing treatment. In terms of posterior glenohumeral instability, the 'gamma angle concept' can help ascertain which lesions are prone to recurrence based on the sum of specific angles and millimetres of posterior glenoid bone loss, in a similar fashion to what happens in anterior shoulder instability. Cite this article: EFORT Open Rev 2018;3:632-640. DOI: 10.1302/2058-5241.3.180028